Intercultural competence measurement tools for Indonesian students: Adaptation, testing construct validity, and measurement invariance with the MIMIC model - Arlianto, Arlianto; Prahoro, Alfedro Putut; Oktavia, Aini (Jurnal Psikologi, 2024)
Background: Intercultural competence (IC) is a crucial ability, especially in the current context of increased social mobility and globalization. However, it's alarming that no IC instrument or measurement tool adaptation and psychometric property testing has been found in Indonesia, particularly among the student population. This absence highlights a significant gap in research that needs to be addressed.Purpose: This study aims to adapt and test the psychometric properties of an intercultural competence instrument for Indonesian students.Method: 589 students from public and private universities in Indonesia with various socio-demographic backgrounds participated by completing the Intercultural Competence Self-assessment (ICSa) and the Intercultural Effectiveness Scale (IES) that has been adopted into the Indonesian version. The data we obtained from all participants was analyzed using Confirmatory Factor Analysis (CFA) and the MIMIC models.Findings: The analysis results showed that both instruments meet the model fit index, but the data produced by IES is more susceptible to measurement invariance than ICSa.Implication: For future research, we suggest 1) exploring the dynamics of socio-demographic variables in the development of students' intercultural competence and 2) Survey studies using IC instruments that we have adapted to consider socio-demographic data as covariates when conducting statistical analysis.